Analisis Implementasi Pembiayaan Kredit Usaha Rakyat (KUR) Syariah dalam Meningkatkan Pendapatan UMKM: Studi Kasus pada Pegadaian Cabang Mandala - Mulyani, Seri; Jannah, Nurul; Syafina, Laylan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study employs a descriptive qualitative methodology, using field research. The objective of this research is to determine the impact of Pegadaian's involvement in enhancing the revenue of micro, small, and medium companies (UMKM) through the utilization of Shariah People's Enterprise Credit (KUR). This study employs interviews, observations, and documentation as methods for data collection. This research demonstrates the significant role of Kur Shariah Pegadaian in facilitating small and medium-sized companies (UMKM) in acquiring the necessary finance for company expansion and development. In addition, the Kur shariah pegadaian significantly boosts the profits or revenue of small and medium-sized firms (UMKM) to a far greater extent than previously.